Integrating Mobile-Based Learning in Teaching English Skills at ESP Classroom - Siska Amelia Maldin (Journal of English Language Teaching, 2022)
Teaching four notions of English for Specific Purposes (ESP) skills like listening, speaking, reading, and writing at vocational higher education seems challenging even if the class is conducted offline or online. The specialty can be seen in designing the learning process based on 60% practical with 40% theory. Unfortunately, the disruptions are discovered in several ESP classrooms where inadequate materials, less interactive learning process, and drilling reluctance contribute to students’ lower motivation, willingness to learn, and anxiety. Hence, an effective strategy is needed to occupy the students’ needs, especially those students with a high level of boredom in learning a language. Thus, mobile-based learning is proposed to answer the challenge. This learning strategy is formed by maximizing the use of mobile-phone technology in the ESP classroom. By applying mobile-based learning in teaching the four skills, it is perceived that the students are going to get great access to material while they were asked to learn through this technique, in a more communicative learning experience which can increase their creativity and eagerness to learn. Therefore, this research is designed in a qualitative approach through library research with the purpose to describe and present the strategies to assemble the ideas of creating communicative classes by using mobile phone technology.